(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the author considers the main reasons of crime of minors. The crime of minors is a consequence of the certain negative phenomena existing in our society. Key words: crime among minors, the causes of juvenile delinquency, prevention of juvenile delinquency.